2021
DOI: 10.1002/adfm.202009949
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Control of Long‐Range Cationic Ordering in the Synthesis of Layered Ni‐Rich Oxides

Abstract: Deciphering the sophisticated interplay between thermodynamics and kinetics of high‐temperature lithiation reaction is fundamentally significant for designing and preparing cathode materials. Here, the formation pathway of Ni‐rich layered ordered LiNi0.6Co0.2Mn0.2O2 (O‐LNCM622O) is carefully characterized using in situ synchrotron radiation diffraction. A fast nonequilibrium phase transition from the reactants to a metastable disordered Li1−x(Ni0.6Co0.2Mn0.2)1+xO2 (D‐LNCM622O, 0 < x < 0.95) takes place while l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
66
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 56 publications
(63 reference statements)
6
66
0
Order By: Relevance
“…Liu and co‐workers employed in situ high‐temperature synchrotron radiation diffraction (HTSRD) to systematically investigate the nonequilibrium formation of layered NCM622 (Figure 6c). [ 37 ] The starting reactants are the TM‐hydroxide Ni 0.6 Co 0.2 Mn 0.2 (OH) 2 (NCM622OH) precursor with trigonal layered structure ( P true3¯ m 1, T1 phase), and lithium source LiOH·H 2 O. The in situ HTSRD pattern shows that the characterized reflections of NCM622OH gradually disappear when the temperature increases to 300 °C.…”
Section: Degradation Mechanismsmentioning
confidence: 99%
“…Liu and co‐workers employed in situ high‐temperature synchrotron radiation diffraction (HTSRD) to systematically investigate the nonequilibrium formation of layered NCM622 (Figure 6c). [ 37 ] The starting reactants are the TM‐hydroxide Ni 0.6 Co 0.2 Mn 0.2 (OH) 2 (NCM622OH) precursor with trigonal layered structure ( P true3¯ m 1, T1 phase), and lithium source LiOH·H 2 O. The in situ HTSRD pattern shows that the characterized reflections of NCM622OH gradually disappear when the temperature increases to 300 °C.…”
Section: Degradation Mechanismsmentioning
confidence: 99%
“…Generally, the layered transition metal oxides, including NCM and LMLOs, are synthesized by using a co-precipitation method followed by a high-temperature solid-state reaction. [23][24][25][26][27] The nano-sized primary particles tend to agglomerate to form micron-sized spherical secondary particles during the co-precipitation process, concomitant with the formation of voids inside the secondary particles. [28,29] The agglomerates provide a reduced diffusion length for Li-ions within their primary particles and an increased number of pores, which facilitate the transport of Li-ions and enhance the rate capability of cathode materials.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to quartz capillaries, where molten LiOH (m.p. 735 K at 1 atm) (1 atm = 101 325 Pa) reacts with SiO 2 to yield side products such as Li 2 SiO 3 or Li 4 SiO 4 , (Bianchini et al, 2020;Wang et al, 2021), no additional peaks were observed in the PXRD measured in sapphire capillaries. Alkaline earth silicate wool was used as a plug material instead of quartz.…”
Section: Gas-flow Reactor For In Situ Diffractionmentioning
confidence: 99%
“…Thus, it is crucial to understand the interplay of thermodynamics and kinetics to engineer the materials' crystallinity and primary particle size. Two recent studies of the formation of LiNiO 2 (Bianchini et al, 2020) and LiNi 0.6 Co 0.2 Mn 0.2 O 2 (Wang et al, 2021) showed that the reaction proceeds from a layered TM hydroxide through a 3D condensed intermediate phase to the final layered structure. Additionally, there is a strong correlation between easily observed lattice parameters and crystallite size, as well as chemical processes such as Ni 2+ to Ni 3+ oxidation or site ordering inside the unit cell.…”
Section: Gas-flow Reactor For In Situ Diffractionmentioning
confidence: 99%
See 1 more Smart Citation